The impact of comorbidities on costs, utilities and health-related quality of life among HIV patients in a clinical setting in Bogotá (2017)
Background: This study aimed to assess the impact of comorbidities (CMs) on costs, utilities and health-related quality of life (HRQOL) among HIV patients in Colombia. Methods: A cross-sectional study was conducted among 138 HIV patients at an outpatient clinic in Bogotá to assess their costs, utilities (EQ5D-5L) and HRQOL (EQ-VAS). CMs and other covariates were gathered from patient records. Multiple regression models were conducted to assess the impact of CMs. Results: Of all patients, 72% experienced CMs; of these, half experienced ?2 CMs (N = 49). CMs had a statistically significant impact on utilities when the EQ5D-5L (P = 0.022) was applied among patient with ?2 CMs. No statistical significance was found for the impact of CMs on costs. Conclusion: This study suggests that having multiple CMs significantly influences utility, and CMs have some impact on HRQOL measured using the EQ-VAS but this effect is at the border of significance. No significant impact was observed on costs. © 2016 The Author(s). Published by Informa UK Limited, trading as Taylor and Francis Group.